Stop and Branch Behaviors of Geniculocortical Axons: A Time-Lapse Study in Organotypic Cocultures - Yamamoto, Nobuhiko (J Neurosci, 1997)
The behavior of growing thalamic axons was studied in an organotypic coculture of the lateral geniculate nucleus (LGN) with the visual cortex (VC) to reveal cellular interactions that underlie the formation of lamina-specific thalamocortical connections. The LGN explant was placed at the ventral side, pial surface, or lateral edge of the VC explant, and fluorescent dye-labeled LGN axons were observed by confocal microscopy in fixed and living tissue. The axonal projection pattern in fixed cocultures after 1 week in vitro demonstrated that, in all three configurations, LGN axons formed primitive branches mainly in layer 4. A time-lapse study further examined axonal growth and branch formation in the living cortical explant. The majority of branches emerged within layer 4 behind the axonal tip, regardless of the direction of axonal entry. In addition, most axons entering from the ventral or pial side of the VC exhibited a transient or persistent stop of axonal growth in and around layer 4, whereas those entering from the lateral edge of the VC traveled along layer 4 without exhibiting stop behavior. The axonal stop often was accompanied by growth cone collapse and a slight retraction. These results suggest the existence of branch and stop cues in layer 4 of the cortex that are recognized by LGN axons.